Notes on Subextraction and Labeling Algorithm - Kwon, Kiyang (Journal of Language Sciences, 2015)
The goal of this paper is to show the explanatory power of labeling algorithm in Chomsky(2013, 2014) and consider the correlation between subextraction and labeling algorithm. Especially, we will consider how the effects of Condition on Extraction Domain and Freezing effects can be made under the theory of labeling algorithm in Chomsky(2013, 2014) and Goto(2015). Especially, we will investigate the correlation between labeling and extraction phenomena in English under the theory of Goto(2015) and point out the problems of Goto’s(2015) analysis of correlation between extraction and labeling. After indicating Goto’s(2015) problems, we will propose that movement over the labeled syntactic object can be allowed, but movement over the unlabeled syntactic object can be disallowed. To prove our proposal, we will suggest the following empirical evidences as follows: (i) the grammatical contrast between PP-raising over wh-element which is the labeled syntactic object and PP-raising over topicalized element which is the unlabeled syntactic object in English (ii) the grammatical contrast between wh-subject raising over T with Agent Focus morpheme and wh-subject raising over T without Agent Focus morpheme in Kaqchikel, a Mayan language of Guatemala KCI Citation Count: 2